(untitled) (GAIMS Journal of Medical Sciences, 2025)
Fibroepithelial polyp is one of the benign lesions of oral cavity which occurs as inflammatory response to local irritation or trauma. Clinically, patients with fibroepithelial polyps present as a painless pedunculated or sessile swelling. They can be treated by simple surgical excision or by other methods such as electrocautery or laser ablation. This is case report of a 48-year-old female who reported to the dental clinic with a soft to firm, painless pedunculated swelling in the left buccal mucosa. This patient underwent an excisional biopsy under local anesthesia. Histological examination confirmed the diagnosis of fibroepithelial polyp. In conclusion, fibroepithelial polyp should be kept as one of the differential diagnoses of benign soft tissue lesions of the oral cavity.